41.4k views
5 votes
Please help, 40 points.

Please help, 40 points.-example-1
User Tom Finet
by
5.2k points

2 Answers

3 votes

Answer:

4th choice

Explanation:

To start, let's simplify all the radicals. 72 is 6^2 * 2, so taking the square root gives 6sqrt2. 27 is 3^2 * 3, and taking the square root gives 3sqrt3. 8 is 2sqrt2, and 2 * 2sqrt2 is 4sqrt2, so now, doing all of the operations, we get 10sqrt2 - 3sqrt3 or the 4th choice.

User Mathieu
by
5.1k points
3 votes

Answer:

10sqrt(2) -3sqrt(3)

Explanation:

sqrt(72) - sqrt(27) + 2sqrt(8)

We know that sqrt(ab) = sqrt(a) sqrt(b)

sqrt(72) = sqrt(36*2) = sqrt(36) sqrt(2) = 6sqrt(2)

sqrt(27) = sqrt(9*3) =sqrt(9) sqrt(3) = 3sqrt(3)

sqrt(8) = sqrt(4*2) = sqrt(4) sqrt(2) = 2sqrt(2)


sqrt(72) - sqrt(27) + 2sqrt(8)

Replace with the above

6sqrt(2) -3sqrt(3) +2(2sqrt(2))

Combine like terms

6 sqrt(2) -3sqrt(3) +4sqrt(2)

10sqrt(2) -3sqrt(3)

User Ako
by
5.9k points